Work and Technological Innovation in the Retail Sector. The Case of Fast Fashion Stores in Italy - Manzo, Cecilia; Fullin, Giovanna; Bianconi, Beatrice (Italian Sociological Review, 2024)
The impact of technological innovation on employment has been a subject of extensive study, particularly regarding job polarization, where routine, medium-skilled jobs are more likely to be automated compared to high-skilled and manual jobs. However, medium-skilled jobs requiring face-to-face interaction, such as those in the retail sector, are less susceptible to automation. This article examines how technological innovation is transforming the roles of frontline service workers in the retail sector, focusing on sales assistants in the fast fashion industry in Milan. Retail is not a leading industry in technological innovation, making it a suitable example for studying gradual changes in job roles due to technology. The research investigates how the integration of online sales and digital tools has impacted the work organization and job quality of sales assistants. Despite the rise in online sales, brick-and-mortar stores have not been entirely replaced, but the nature of in-store work has become more complex. Drawing on three strands of literature—technology’s impact on employment, digitalization and algorithmic management, and job quality—the study uses interviews with workers, managers, and trade unionists and maps recent changes that occurred in fast fashion stores. Findings reveal that technological innovation in retail has made sales assistants’ jobs more demanding but has not necessarily improved job quality or wages, highlighting a need for better training and economic recognition to support these workers through the ongoing transformations.